(untitled) (Nigerian Journal of Pharmaceutical Research, 2025)
Background: The pharmaceutical sector in West Africa is faced by challenges due to limited domestic capacity for production of medicines and heavy reliance on imports. Local pharmaceutical manufacturers face challenges such as high cost of doing business, poor infrastructure, and lack of standardized equipment. This study aims to assess the perception towards local manufacturing of Active Pharmaceutical Ingredients (APIs) in West Africa and explore strategies to improve access to medicines and achieve self-reliance in the region. Methods: A cross-sectional survey was conducted amongst stakeholders that attended a conference targeted at improving local manufacturing of APIs in West Africa. Online and physical data were collected through the use of a validated questionnaire. Retrieved data were analyzed using Statistical Package for Social Sciences version 25. Data were presented in form of tables, frequencies, percentages and chi square analysis was used for inferential statistics. Results: A total of 191 valid responses were received. Close to half (48.2%) of the stakeholders were female, majority of the study participants were between the ages of 18 and 40 years and were educated up to bachelor’s degree level (62.8% and 58.1% respectively). The majority of participants (85.5%) acknowledged significant gaps in access to medicines and essential pharmaceutical commodities in West Africa. Over two-thirds of the respondents (83.3%) believed that West Africa is suitable for cost-effective production of quality medicines and majority of them (83.0%) were willing to patronize locally manufactured APIs. Conclusion: Findings from this study identifies significant gaps with access to medicines and essential pharmaceutical commodities in the region and suggests the need for more strategic investments and policy action towards the promotion of local API production in the region.